PERKEMBANGAN PENAFSIRAN DELIK MAKAR DALAM KUHP DI INDONESIA - Ristanti, Yuni; Parman, Lalu; Ufran, Ufran (Kertha Semaya : Journal Ilmu Hukum; Vol 10 No 1 (2021)DO - 10.24843/KS.2021.v10.i01.p03, 2021)
Tujuan penelitian untuk mengetahui dan mengenalisis perkembangan penafsiran delik Makar dalam KUHP di Indonesia. Adapun metode penelitian yang digunakan adalah penelitian hukum normatif. Hasil  penelitian diperoleh bahwa makar terdapat pada pasal 87, 104, 106, 107, 110 KUHP. Permulaan perbuatan makar dalam KUHP sudah disebut sebagai delik makar. Pengertian makar berdasarkan penafsiran hakim pada masa pemerintahan presiden Joko Widodo adalah ancaman membunuh presiden melalui sosial media dan makar menggulingkan pemerintah melalui materi gugatan atau disebut makar melalui pengadilan. Segala bentuk perbuatan selama tujuannya untuk makar sesuai pasal-pasal 104, 106, 107 KUHP disebut sebagai delik makar. The purpose of the study was to identify and identify the development of the interpretation of the Makar offense in the Indonesian Criminal Code. The research method used is normative legal research. The results showed that treason is found in articles 87, 104, 106, 107, 110 of the Criminal Code. The beginning of the act of treason in the Criminal Code is already referred to as a treason offense. The definition of treason based on the interpretation of judges during the reign of President Joko Widodo is the threat to kill the president through social media and treason to overthrow the government through lawsuits or called treason through the courts. All forms of action as long as the purpose is to commit treason in accordance with articles 104, 106, 107 of the Criminal Code are referred to as treason offenses.